Chemical constituents of Blumea balsamifera. (June 2021) - Hanh, Tran Thi Hong; Hang, Le Thi Thuy; Huong Giang, Vu; Trung, Nguyen Quang; Thanh, Nguyen Van; Quang, Tran Hong; Cuong, Nguyen Xuan
Graphical abstract: Highlights: Ten secondary metabolites were isolated from Blumea balsamifera . Three new compounds (1 ―3 ) were elucidated by NMR and HR-ESI-QTOF mass spectra. Their cytotoxicity against five human cancer cell lines was evaluated by SRB assay. Abstract: Phytochemical investigations of Blumea balsamifera branches and leaves led to the isolation of ten secondary metabolites, including three new compounds, namely, balsamiferine K (1 ) and balsamiferosides A (2 ) and B (3 ). Structural elucidation was confirmed by detailed analysis of the 1D and 2D NMR spectra as well as HR-ESI-QTOF mass spectra. Among the isolated compounds, blumeaene J (4 ) exhibited moderate cytotoxicity against LNCaP (IC50 = 44.53 ± 4.95 μM) and SK-Mel2 (IC50 = 46.49 ± 3.84 μM) cell lines and weak effects on HepG2 (IC50 = 61.54 ± 2.98 μM), KB (IC50 = 65.40 ± 4.97 μM), and MCF-7 (IC50 = 70.06 ± 5.65 μM) cell lines, whereas (―)-angelicoidenol 2- O - β -d -glucopyranoside (6 ) revealed weak activity on all five tested cancer cell lines, with IC50 values ranging from 61.60 ± 5.64–98.73 ± 2.24 μM.